Measurements of branching fractions and CP-violating asymmetries in B meson decays to charmless two-body states containing a K-0 - Aubert, B; Barate, R; Boutigny, D; Couderc, F; Gaillard, J; Hicheur, A; Karyotakis, Y; Lees, J; Robbe, P; Tisserand, V; Zghiche, A; Palano, A; et al. (2004)
The branching fractions and CP violating charge symmetries for B + → K0π+ and B0→K 0π0 were measured. The decays values for B 0→K̄0K0 and B0→K 0K̄0 were investigated. The upper limits on their branching functions were set at 2.5×10-6 and 1.8×10 -6 respectively, at the 90% CL. It was found that the branching fraction were consistent with previous measurements of the same quantities, but had nearly twice the statistical precision.